ANALISIS PENCEMARAN Cr(VI) DI SUNGAI BADEK, KOTA MALANG DENGAN MENGGUNAKAN BIOFILM - Andi Kurniawan; Lutfi Ni'matus Salamah; Putri Dwiyan Jayati (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2019)
One of the most severe environmental problems is heavy metal pollution such as Cr(VI) in aquatic ecosystems. Cr(VI) is toxic and carcinogenic heavy metals pollutants that persistent and easily accumulated through the food web. Accumulation of Cr(VI) concentration in the aquatic ecosystem gradually increases with the increases of industrial activity. Therefore, Cr(VI) concentration in aquatic ecosystems should be monitored continuously, and thus, suitable and accuracy monitoring technologies are necessary. This study analyzed the utilization of biofilm as a biomonitoring agent of Cr(VI) in the Badek River, Malang City. The concentration of Cr(VI) inside the biofilm and the surrounding water of biofilm were investigated. The results revealed that the concentrations of Cr(VI) inside the biofilms were hundred times higher than the surrounding water. The biofilm may accumulate Cr(VI) from the surrounding water resulting in the Cr(VI)-rich microenvironment inside the biofilm. The adsorbed Cr(VI) is retained mostly in the interstitial water of the biofilm matrices. The findings in this study suggested that the biofilm can be used as a potential biological agent to monitor of Cr(VI) pollutant in the river ecosystems.